Design and Implementation of Water Monitoring Program in Peatlands IoT Based - Rahajoeningroem, Tri; Nugraha, Soni (International Journal of Research and Applied Technology (INJURATECH), 2023)
Forests and peatlands in Indonesia are experiencing constant degradation, caused mainly by farming activities, illegal logging, and forest fires. One way of addressing this problem is to restore the hydrology of the forest and peatland ecosystems through the monitoring water table and blocking the ditches and canals. Monitoring the water table aims to observe the groundwater level in the peatland area before and after the canal blocking was built. Building blocks and dams, it is expected that the water level and retention in the ditches and canals and nearby forest and peatlands will increase, reducing the danger of fire during the dry season and improving the possibility of rehabilitating nearby degraded land. An approach for a water monitoring program is based on a water level control system and hydrology logger. This large amount of water runoff will be monitored through high surface water data storage devices. The process of monitoring the water level is done continuously with integrating systems using IoT to obtain the latest condition data of hydrological variables in the field from a distance to be done various actions needed to avoid peatland forest fire